Electrochemical detection of pesticides: A comprehensive review on voltammetric determination of malathion, 2,4-D, carbaryl, and glyphosate - Andualem Ejigu; Molla Tefera; Atnafu Guadie (Electrochemistry Communications)
Pesticides are widely used in agriculture to protect crops from diseases, insects, and weeds. However, a significant portion of these pesticides fail to reach their intended destination and instead contaminate the soil and water sources. As interest in on-site analyte detection continues to grow, alternative methods of pesticide measurement have gained considerable attention. This review focuses on the electrochemical detection of four important pesticides: malathion, 2,4-dichlorophenoxy acetic acid, glyphosate, and carbamates, utilizing a variety of electrochemical sensing techniques, electrode materials, electrolyte media, and sample arrays. By summarizing various electrochemical studies, the review provides an overview of reported analytical results, including limits of detection and linearity ranges. The article highlights recent advances in the electrochemical detection of selected pesticides and addresses the challenges and efforts involved in achieving electrochemical detection suitable for field applications.